2006
DOI: 10.1038/sj.cr.7310117
|View full text |Cite|
|
Sign up to set email alerts
|

Selenoprotein expression is regulated at multiple levels in prostate cells

Abstract: Selenium supplementation in a population with low basal blood selenium levels has been reported to decrease the incidence of several cancers including prostate cancer. Based on the clinical findings, it is likely that the antioxidant function of one or more selenoproteins is responsible for the chemopreventive effect, although low molecular weight seleno-compounds have also been posited to selectively induce apoptosis in transformed cells. To address the effects of selenium supplementation on selenoprotein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 23 publications
4
22
1
Order By: Relevance
“…Previously we have shown that PC-3 prostate cancer cells had reduced levels of the selenoprotein GPX1 compared with LNCaP prostate cancer cells and RWPE-1 nontumorigenic prostate cells (even when selenium levels were sufficient) suggesting that eEFSec and SBP2 may be limiting (17). We therefore first tested PC-3 lysates for Sec incorporation activity in the Sf21 system.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we have shown that PC-3 prostate cancer cells had reduced levels of the selenoprotein GPX1 compared with LNCaP prostate cancer cells and RWPE-1 nontumorigenic prostate cells (even when selenium levels were sufficient) suggesting that eEFSec and SBP2 may be limiting (17). We therefore first tested PC-3 lysates for Sec incorporation activity in the Sf21 system.…”
Section: Resultsmentioning
confidence: 99%
“…Sec , HepG2 cells were grown to 80% confluence in DMEM supplemented with 50 nM sodium selenite, which is the dose typically used to support maximal selenoprotein production without toxic effects (46).…”
Section: Stoichiometry Of the Sepsecs-trna Sec Complex In Vivo-for Qumentioning
confidence: 99%
“…Our results obtained in Hek293 cells recapitulated what has been reported in other studies, either in rodents 20,32 or in human. 33 Interestingly, when comparing Dpl with Unsup extracts, the selenium deficiency led to a dramatic decrease of both Gpx1 and Gpx4 expression, although in the Dpl extract Gpx4 was still detectable while Gpx1 had almost disappeared. This effect uniquely depended on selenium concentration since cell growth in Dpl + Se media restored the expression of both Gpx1 and Gpx4 to the levels observed in Sup media.…”
Section: Introductionmentioning
confidence: 99%